The year 2021 in COVID-19 pandemic in children - Elena Bozzola; Carlo Caffarelli; Francesca Santamaria; Giovanni Corsello (BMC, 2022)
Abstract In this article, the developments in the field of COVID-19 pandemic published in the Italian Journal of Pediatrics in 2021 are reflected. We describe progresses in SARS-CoV-2 transmission route, clinical presentation, diagnosis, treatment, and access to health care facilities in children. They led to substantial changes in the clinical approach.